Changes in physiological, functional and structural markers of cystic fibrosis lung disease with treatment of a pulmonary exacerbation. Issue 6 (9th February 2013) - Horsley, Alex R; Davies, Jane C; Gray, Robert D; Macleod, Kenneth A; Donovan, Jackie; Aziz, Zelena A; Bell, Nicholas J; Rainer, Margaret; Mt-Isa, Shahrul; Voase, Nia; Dewar, Maria H; Saunders, Clare; et al.
Abstract : Background: Clinical trials in cystic fibrosis (CF) have been hindered by the paucity of well characterised and clinically relevant outcome measures. Aim: To evaluate a range of conventional and novel biomarkers of CF lung disease in a multicentre setting as a contributing study in selecting outcome assays for a clinical trial of CFTR gene therapy. Methods: A multicentre observational study of adult and paediatric patients with CF (>10 years) treated for a physician-defined exacerbation of CF pulmonary symptoms. Measurements were performed at commencement and immediately after a course of intravenous antibiotics. Disease activity was assessed using 46 assays across five key domains: symptoms, lung physiology, structural changes on CT, pulmonary and systemic inflammatory markers. Results: Statistically significant improvements were seen in forced expiratory volume in 1 s (p<0.001, n=32), lung clearance index (p<0.01, n=32), symptoms (p<0.0001, n=37), CT scores for airway wall thickness (p<0.01, n=31), air trapping (p<0.01, n=30) and large mucus plugs (p=0.0001, n=31), serum C-reactive protein (p<0.0001, n=34), serum interleukin-6 (p<0.0001, n=33) and serum calprotectin (p<0.0001, n=31). Discussion: We identify the key biomarkers of inflammation, imaging and physiology that alter alongside symptomatic improvement following treatment of an acute CF exacerbation. These data, in parallel with our study of biomarkers in patients with stable CF, provide important guidance in choosing optimal biomarkers for novel therapies. Further, they highlight that such acute therapy predominantly improves large airway parameters and systemic inflammation, but has less effect on airway inflammation.